The Effects of Plasticizer Types on Properties of Whey-Gelatin Films - Fahrullah Fahrullah; Djoko Kisworo; Bulkaini Bulkaini; Haryanto Haryanto; Baiq Rani Dewi Wulandani; Wahid Yulianto; Azhary Noersidiq; Vebera Maslami (Jurnal Biologi Tropis, 2023)
Edible film is an alternative packaging that can be applied to food because it has biodegradable properties. The use of plasticizers can be used in the manufacture of edible films to increase the flexibility and densibility of the film. This study aims to determine the effect of plasticizer type on the thickness, WVTR, and moisture content of whey-gelatin film blends. The research was conducted in a Completely Randomized Design with three treatments, treatments that make a difference are tested with Duncan's Multiple Range Test (DMRT). The treatment used different plasticizer (P1G: Glycerol; P1S: Sorbitol; and P1P: polyethylene glycol (PEG) 400). The properties of whey-gelatin films showed that thickness was at 0.0350-0.0352 mm; the WVTR was at 4.87-6.22 g/m2/day; the water content was at 12.55-15.69%. The use of glycerol as plasticizer produced the best edible film characteristics compared to sorbitol and PEG 400 with a thickness value of 0.0350 mm; WVTR of 6.22 g/mm2/day and moisture content of 12.55%.